2021
DOI: 10.1007/s00167-021-06475-1
|View full text |Cite
|
Sign up to set email alerts
|

Latarjet procedure enables 73% to return to play within 8 months depending on preoperative SIRSI and Rowe scores

Abstract: Purpose Systematic reviews report return to play (RTP) within 5.8 months (range, 3–8) following the Latarjet procedure, but the factors that influence RTP remain unknown. The present study aimed to report the rate and time of return to play (RTP) during the first 8 months following the Latarjet procedure, and to determine the influence of sport type or patient characteristics. Methods The authors retrospectively collected the records of patients that under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
1
15
0
2
Order By: Relevance
“…12,14-16 Hurley et al 14 found that patients who did not return to sports after ABR showed lower mean SIRSI scores than those who returned to sports (39.8 vs 68.9, respectively). Moreover, Bohu et al 5 found that the likelihood of return to sports after a Latarjet procedure was significantly associated with preoperative SIRSI scores. In line with these studies, we found that those who returned to sports were more psychologically ready to return to play than those who did not return after shoulder instability surgery (76.8% vs 4.5%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12,14-16 Hurley et al 14 found that patients who did not return to sports after ABR showed lower mean SIRSI scores than those who returned to sports (39.8 vs 68.9, respectively). Moreover, Bohu et al 5 found that the likelihood of return to sports after a Latarjet procedure was significantly associated with preoperative SIRSI scores. In line with these studies, we found that those who returned to sports were more psychologically ready to return to play than those who did not return after shoulder instability surgery (76.8% vs 4.5%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Although the SIRSI score has been reported in the literature, 5,12,14-16,26 only some studies analyzed its association with return to sports. 12,14-16 Hurley et al 14 found that patients who did not return to sports after ABR showed lower mean SIRSI scores than those who returned to sports (39.8 vs 68.9, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 73 per cent of patients continued their pre-injury sports eight months after the procedure. 15 The Latarjet method has multiple mechanisms for increasing anterior stability. The Bankart lesion is repaired, providing stability, and the transfer of the coracoid process extends the bony articular arc of the glenoid.…”
Section: Introductionmentioning
confidence: 99%